Mcgraw-hill concise encyclopedia of engineering (New York, 2005)
Hundreds of well-illustrated articles explore the most important fields of science. Based on content from the McGraw-Hill Concise Encyclopedia of Science & Technooogy, Fifth Edition, the most widely used and respected science reference of its kind in print, each of these subject-specific quick-reference guides features: Detailed, well-illustrated explanations, not just definitions, Hundreds of concise yet authoritative articles in each volume
Keywords: Engineering; Encyclopedias